Robust beamforming for multicell downlink TDD massive MIMO system based on QoS - Jie CAO; Yong LIAO; Xuan-fan SHEN (Tongxin xuebao)
In view of multicell downlink time division multiplexing (TDD) massive multiple-input multiple-output (MIMO) systems which had imperfect channel state information (CSI),the beamforming problem that minimized the total transmit power and signal leakage power based on quality of service (QoS) was studied.First,the objective problem was approximated as a standard convex optimization problem.Then,by using the duality of uplink and downlink,an inner and outer layer iterative algorithm was proposed.Numerical results show that,comparing with other typical downlink multicell massive MIMO beamforming algorithms,the proposed algorithm has obvious advantages in terms of complexity and energy efficiency.